A three-year study on periodontal microorganisms of short locking-taper implants and adjacent teeth in patients with history of periodontitis. (April 2020) - Yan, Xia; Lu, Hongye; Zhang, Li; Zhu, Bin; Piao, Muzi; Huang, Baoxin; Zhang, Haidong; Meng, Huanxin
Abstract: Objective: To analyze the change of six periodontal pathogens around short locking-taper implants and adjacent teeth in patients with different periodontal conditions for three years. Methods: Sixty implants and 62 adjacent teeth from 24 patients with different periodontal conditions were included: 5 patients with history of aggressive periodontitis (AgP group), 14 patients with history of chronic periodontitis (CP group), and 5 patients with healthy condition or slight gingivitis (H group). Subgingival samples were collected at five timepoints: before implant placement (T1); before second stage operation (T2); one month after restoration (T3); one year after functional loading (T4) and two years after functional loading (T5). Porphyromonas gingivalis, Treponema denticola, Tannerella forsythia, Fusobacterium nucleatum, Prevotella intermedia, and Aggregatibacter actinomycetemcomitans were detected by polymerase chain reaction (PCR). Results: Pathogens were hardly found around implants or adjacent teeth until T4. The detection rates of five pathogens other than A. actinomycetemcomitans raised up from T3 to T5. F. nucleatum and P. gingivalis were mostly detected followed by P. intermedia, T. forsythia, and T. denticola . The detection rate of P. gingivalis in implants were higher than natural teeth. There was significant correlation between pathogenic bacteria from implants and adjacent teeth. A. actinomycetemcomitans were only detected positively in peri-implant sites of AgP group. Peri-implantitis sites showed significantly higher detection rates of T. denticola, F. nucleatum at T4, and P. gingivalis, F. nucleatum at T5 than peri-implant mucositis and healthy groups. Conclusion: This three-year longitudinal study demonstrated that periodontal pathogens accumulate over time around short locking-taper implants and adjacent natural teeth after restoration. Adjacent teeth may become the microbial reservoir for peri-implant bacteria. Therefore, periodontally compromised patients may face higher risk for peri-implant disease. Clinical significance: Plaque control of implant should be intensified with time instead of diminished. Patients with history of periodontitis need more frequent and individualized implant maintenance. Treatment and maintenance for adjacent teeth is as important as for implants..